Basilar artery thrombosis due to hyperhomocysteinemia treated conservatively: a therapeutic success - Sharma, Deepak; Atam, Virendra; Majumdar, Avirup; Hashim, Mohammed (International Journal of Advances in Medicine, 2020)
Basilar artery thrombosis is a rare and potentially fatal cause of posterior circulation stroke. Among the various etiologies, hyperhomocysteinemia is crucial and often under diagnosed, especially in developing countries. Authors describe the case of a 15-year male who presented with 1-day history of headache, vomiting and altered mental status. Non-contrast CT Head revealed multiple acute infarcts in posterior circulation of brain. Laboratory investigations revealed hyperhomocysteinemia. Contrast enhanced MRI Brain showed acute infarcts in bilateral cerebellar hemispheres, pons, midbrain, medulla and vermis. MR venography was suggestive of Basilar Artery thrombosis. Thrombolysis was not done due to delayed presentation; hence authors resorted to conservative management with folic acid and vitamin B supplementation. The patient showed gradual clinical improvement and had complete clinical recovery during follow up visit. A favorable outcome with conservative management of basilar artery thrombosis is rarely reported in literature.